2019
DOI: 10.1002/mawe.201900048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the jet velocity on the weld quality of magnetic pulse welded dissimilar sheet joints of aluminum and steel

Abstract: The object of this investigation is to determine the influence of the jet velocity on the weld quality of sheet joints produced via magnetic pulse welding. The use of a suitable high-speed camera system enables to observe the jet in detail, to determine its velocity during the collision process and to compare them to the achieved qualities (tensile strength, weld seam characteristics) of the welded samples. The results show that the quality of the weld generally correlates with the jet velocity, however the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Zhang et al (2008) also observed excessive plastic deformation and spalling along the flyer–target joint interface in MPW AA6061 tubes and attributed the same to the generation of high intensity stress waves due to the application of a very high peak discharge current of 860 kA [23]. A jetting velocity of around 34.64 mm s −1 was also reported favourable to achieve good MPW joints between aluminium and steel sheets [24].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al (2008) also observed excessive plastic deformation and spalling along the flyer–target joint interface in MPW AA6061 tubes and attributed the same to the generation of high intensity stress waves due to the application of a very high peak discharge current of 860 kA [23]. A jetting velocity of around 34.64 mm s −1 was also reported favourable to achieve good MPW joints between aluminium and steel sheets [24].…”
Section: Resultsmentioning
confidence: 99%
“…Affected by a collision angle, a point of collision (PoC) moves along the colliding surfaces. When the dynamic elastic limit of the material is exceeded, material flow results from the plastic deformation of the contact surfaces, and a stream of material is pushed ahead of the PoC [79,80]. This so-called jetting removes brittle oxide layers and surface contaminations from the surfaces, which are ejected either as a compact stream or as a dispersed cloud of particles (CoP) [81].…”
Section: Magnetic Pulse Weldingmentioning
confidence: 99%